Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
first make the equation to slope intercept
y=1/2-1/12
the slope of the perpendicular is equal to the negative inverse
m=-2
now substitute known variable in slope intercept form
-2/3=-2(1/2)+b
-2/3=-1+b
b=1/3
y=-2x+1/3
in standard
6x+3y=1
y=1/2-1/12
the slope of the perpendicular is equal to the negative inverse
m=-2
now substitute known variable in slope intercept form
-2/3=-2(1/2)+b
-2/3=-1+b
b=1/3
y=-2x+1/3
in standard
6x+3y=1
Given:
equation of line l : 6x -12y =1
Converting the equation to slope-intercept form , we get,
-12y = 1 - 6x
y = [tex] \frac{-6x+1}{-12} [/tex]
y = (1/2)x - (1/12)
Now, The when you find the equation of a perpendicuilar line, then the slope is the negative reciprocal of the slope of the given line. So,
y = -2x + b..........we didn't put anything for y-intercept because we don't know the y intercept of the perpendicular line yet.
Now, plugging the points from the question into the equation of perpendicular line, we get,
(-2/3) = -2*(1/2) + b
(-2/3) = -1 + b
(-2/3) + 1 = b
(1/3) = b
Now, plugging the value of b in the equation, we get,
y = -2x + (1/3).........this is your required equation
equation of line l : 6x -12y =1
Converting the equation to slope-intercept form , we get,
-12y = 1 - 6x
y = [tex] \frac{-6x+1}{-12} [/tex]
y = (1/2)x - (1/12)
Now, The when you find the equation of a perpendicuilar line, then the slope is the negative reciprocal of the slope of the given line. So,
y = -2x + b..........we didn't put anything for y-intercept because we don't know the y intercept of the perpendicular line yet.
Now, plugging the points from the question into the equation of perpendicular line, we get,
(-2/3) = -2*(1/2) + b
(-2/3) = -1 + b
(-2/3) + 1 = b
(1/3) = b
Now, plugging the value of b in the equation, we get,
y = -2x + (1/3).........this is your required equation
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.